Resistance test of five cocoa (Theobromae cacao L.) clones in South Sulawesi against Phytophthora palmivora. Issue 1 (April 2020) - Dewi, V S; Asman, A; Josua, K; Hamdayanty, H
Abstract: This research aimed to find out the response of some superior cocoa clones in South Sulawesi to Phytophthora palmivora . This research covers several stages ranging from selection and sampling of cocoa clones, pathogen exploration to cocoa clones resistant test with various methods that were inoculated the infected to the healthy cocoa pod, inoculated P. palmivora suspension to the cocoa surface and inoculated P. Palmiora isolates to the healthy cocoa pod section. The results showed that the resistance of cocoa clones to three inoculation methods showed different areas of spotting on each observation day in which method of attaching the infected pod to the healthy pod, showed the slowest growth in the MO1 cocoa clone with average growth of spots of 46.34 cm 2 /day and the largest was shown in 45 cocoa clone which was 79.67 cm 2 /day indicating each clone is very susceptible to infection P. palmivora . Method of inoculating P. palmivora suspension showed that the slowest growth occurred in S1 cocoa clone that was 5.18 cm 2 /day and largest was shown in MO1 cocoa clone (25.19 cm 2 /day), indicating that each clone is very susceptible, except in the clone S1 is rather resistant. As well as in the method of attaching P. palmivora isolate to the healthy pod, the slowest growth occurred in GTB cocoa clones (15.28 cm 2 /day) and largest in M04 cocoa clones (22.28 cm 2 /day) which indicated that each clone was very susceptible to infection of P. palmivora . The three application methods show that different applications can affect the difference in infection rates in each cocoa pod clone. The spots that arise from infection can occur in various ways.